(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
Diseases among young children are the major causes of morbidity and mortality particularly in the developing countries of the world.Children under five years of age are the most vulnerable section of the society and suffer from highest morbidity. The present study makes an attempt to assess the morbidity pattern among the children of under five years in an urban slum and find out its association with various factors. This descriptive cross-sectional study was conducted for a period of 6 months from September 2013 to February 2014 in an urban slum area of moghbazar in Dhaka city. A house to house survey was conducted and a total of 439 children of under five years were enrolled for the study. Out of total 439 children, 244 (55.6%) were females and 95 (44.4%) were males. Among the children 56.5% were suffered from one or more sickness. Overall health morbidities were more in females 59%. Acute respiratory infection (ARI) 215 (49%) was the commonest morbidity found during study period followed by fever 199 (45.3%), diarrhoeal diseases 160 (36.4%), malnutrition 79 (18%) and helminthiasis 75 (17%). Most of the children of under five years suffered from ARI, fever, diarrhoeal diseases and malnutrition were in the age group of 25-36 months. Helminthiasis was more in the age group of 37-48 months and skin problem was more in the age group of 25-36 months. ARI, diarrhoeal diseases, skin problem and infectious diseases were more in male under five years children while, fever, malnutrition and helminthiasis were more in female under five years children. Accident was more in male under five children and the relation was statistically significant. (p=0.03). A statistically significant association was found in diarrhoeal diseases with monthly family income (p= 0.03) and mother’s occupation (p=0.001) and also between skin problem and mother’s education (p=0.022) and occupation (p=0.000). A statistically significant association was found in morbidity pattern of diarrhoeal diseases, fever and helminthiasis with type of house (p=0.017, p=0.009, p=0.000). No association of morbidity was observed with type of latrine and water source. J. Dhaka National Med. Coll. Hos. 2014; 20 (02) : 21-26